Mammoth to the rescue - Osborne, Mary Pope; Masson, Philippe (London Fox red, 2022)
Jack and Annie travel back in time - wearing only their swimsuits! The tree house lands in the freezing Ice Age and they have to hide from hunters and escape from a great cave bear. But when Jack and Annie are chased by a fierce sabretooth tiger and fall into a hunting trap, they're really stuck. Will anybody come to their rescue?
English stories
Keywords: English fictions